Optimum angles of projection in the throws and jumps - Linthorne, N. (coachesinfo.com)
Although it is possible to calculate the optimum projection angle for any athlete, it is not always easy to do so in practice. The calculation requires knowledge of how the athlete's projection speed changes with projection angle (as in Figures 3 and 6). You need to take very careful measurements using a high-speed video camera of many throws (or jumps) by the athlete over a wide range of projection angles. Such measurements usually require the services of a sports scientist, and the process is time-consuming and expensive. For the coach without the necessary resources, a process of trial-and-error at the training track is a good method of identifying your athlete's optimum projection angle. Most athletes will usually 'home-in' on their optimum projection angle relatively quickly with the aid of a tape measure (to measure their performance) and with the guidance of a coach (to help the athlete maintain good technique while experimenting with different projection angles). A high-speed video analysis is beneficial only to the very best athletes. Elite athletes are closer to their ultimate potential, so expending the time and resources to obtain an extra small improvement in performance may be justified. In the throwing and jumping events, the optimum projection angle is usually considerably less than 45° because the speed an athlete can produce decreases as the projection angle is raised. Unfortunately for the coach, each athlete has a unique curve of projection speed versus projection angle. This means that the optimum projection angle is different for every athlete. However, it is not necessary for the coach to spend a great deal of effort in getting their athletes to throw or jump at the optimum projection angle. Most athletes find their optimum projection angle relatively quickly through trial-and-error, and achieving a high projection speed is much more important than throwing or jumping at the optimum angle.